Existence of Fixed Points of Four Maps for a New Generalized F-Contraction and an Application - Muhammad Nazam; Hassen Aydi; Mohd Salmi Noorani; Haitham Qawaqneh (Journal of Function Spaces)
We initiate the concept of a new generalized F-contraction satisfying some contractive conditions involving four maps on a partial metric space. We set up an example to elucidate our main result. An application is derived where a system of elliptic boundary value equations has a common solution.